Teaching children physical education : becoming a master teacher - Graham, George, 1943- (Champaign, Ill. : Human Kinetics Books, 1992)
This book is about: Sucessful teaching; Planning to maximize learning; Creating an atmosphere for learning; ...
Keywords: Education; Physical education; Physical education for children; Physical education for children -- Study and teaching -- United States; Physical education teachers -- Training of -- United States